Effectiveness of Peer-Assisted Learning in Nursing Student Knowledge and Compliance in the Application of Standard Precautions - Ria Desnita; Defrima Oka Surya (Fakultas Ilmu Keperawatan Universitas Indonesia, 2020)
The learning process in higher nursing education develops student competences, such as applying standard precautions, in providing professional nursing care. To improve student knowledge and compliance related to standard precautions requires innovation from lecturers in providing appropriate learning methods. Peer-assisted learning (PAL) can enhance the active role of students and improve achievement. The PAL method involves senior students as peer teachers who help junior students. Using a questionnaire as an assessment instrument, this study aimed to determine the effectiveness of PAL on knowledge and compliance in the application of standard precautions in student nurses. This study design was quasi experimental with pre and post assessment and a control group design approach. This research was conducted at the D Hospital in Padang, Indonesia, a hospital where students practice. This study was conducted in June–September 2017 with a sample size of 45. Data analysis using paired t-test showed that the average values of the level of knowledge and skills of students in the application of standard precautions before and after PAL methods differed significantly in the intervention group (p= 0.001). In conclusion, PAL can be applied in the learning process of nursing students to increase student achievement. Abstrak Efektifitas Metode Peer-Assisted Learning (PAL) terhadap Tingkat Pengetahuan dan Kepatuhan Mahasiswa Dalam Penerapan Kewaspadaan Standar. Proses pembelajaran dalam pendidikan tinggi keperawatan mengembangkan kompetensi siswa, seperti menerapkan tindakan pencegahan standar, dalam memberikan asuhan keperawatan profesional. Untuk meningkatkan pengetahuan dan kepatuhan mahasiswa terkait kewaspadaan standar, dibutuhkan inovasi dari dosen dalam memberikan metode pembelajaran yang tepat. Peer-assisted learning (PAL) dapat mening-katkan peran aktif siswa dan meningkatkan prestasi. Metode PAL melibatkan mahasiswa senior sebagai peer-teacher yang membantu mahasiswa junior. Menggunakan kuesioner sebagai instrumen penilaian, penelitian ini bertujuan untuk menentukan efektivitas PAL pada pengetahuan dan kepatuhan dalam penerapan kewaspadaan standar pada maha-siswa keperawatan. Desain penelitian ini adalah quasi experiment dengan penilaian pre dan post dan pendekatan control group design. Penelitian ini dilakukan di Rumah Sakit D di Padang, Indonesia, sebuah rumah sakit tempat praktik mahasiswa. Penelitian ini dilakukan pada Juni–September 2017 dengan sampel 45. Analisis data menggunakan paired t-test menunjukkan bahwa nilai rerata tingkat pengetahuan dan keterampilan mahasiswa dalam penerapan kewaspadaan standar sebelum dan sesudah metode PAL berbeda secara signifikan pada kelompok intervensi (p= 0,001). Kesimpulannya, PAL dapat diterapkan dalam proses belajar siswa keperawatan untuk meningkatkan prestasi siswa. Kata kunci: kewaspadaan standar, mahasiswa keperawatan, peer-assisted learning (PAL)